Developing a conceptual framework for the relationship between food security status and mental health among low-income mothers - Liebe, Rachel A.; Adams, Leah M.; Hedrick, Valisa E.; Serrano, Elena L.; Porter, Kathleen J.; Cook, Natalie E.; Misyak, Sarah A. (Frontiers in Sustainable Food Systems, 2023)
Introduction Building household resiliency is one strategy that may help insulate households from the effects of food system volatility that contributes to in food insecurity. A stronger understanding of the relationship between food security and mental health is needed to identify potential factors for intervention to improve household resiliency to food system stressors. Because mothers often make household food decisions, they are an important population for building household resiliency. The purpose of this study was to develop and test a conceptual framework for the relationship between food security and mental health for low-income mothers and to identify potential targets for intervention. Methods A conceptual framework was developed based on the existing literature on mental health and food security, as well as factors that impact both constructs. This framework was tested by a path analysis using data from a 2021 cross-sectional survey of low-income Virginia mothers that used validated scales to assess food security status, indicators of mental and physical health, food coping strategies, and social support. Results and discussion The initial model was systematically adapted to develop the final retained model. The retained model did not include a direct effect of food security on mental health, but highlighted two significant mediators of the relationship, food coping strategies and social support. While the effect of social support was not practically significant, the effects of food coping strategies as a mediator from food security to perceived stress and life satisfaction were small (β = 0.21, 0.14, respectively; p < 0.001). The retained model provides a framework for understanding the relationship between food security and mental health and highlights potential targets for intervention. Notably, reducing the need for mothers to utilize food coping strategies should be targeted on multiple levels to reduce the impact on mental health and ultimately improve resiliency to future food system shocks.